PROF. DR. ALİ SELÇUK BİRİCİK HOCANIN MESLEK YAŞAMI VE COĞRAFYA BİLİMİNE KATKILARI - (:unkn) unknown (My University, 2015)
Marmara Üniversitesi Fen Edebiyat Fakültesi Coğrafya Bölümü’nden2013 yılında emekli olan Prof. Dr. Ali Selçuk Biricik, yaklaşık yarım yüzyılıbulan meslek yaşamıyla coğrafya dünyasının yakından tanıdığı değerlihocalardan biri olup coğrafya bilimine birçok alanda önemli katkılar yapmıştır.Bu makalede hocanın eğitimi ve meslek yaşamı, ilmi şahsiyeti, coğrafya eğitimive öğretimine katkıları, idari ve akademik görevleri özlü bir şekilde ifadeedilmiş ve bilimsel yayınları açık künyeleriyle birlikte verilmiştir. Şüphesizbundan sonrada ülkemizin farklı yörelerinde ve coğrafya biliminin çeşitlikonularında çalışma yapmanın yanı sıra yine meslektaşları ve öğrencileriylebirlikte olmayı sürdürecektir. Nitekim emekli olmasına rağmen bugün de aynıistekle çalışmalarına devam etmesi, onun mesleğine olan saygısının vecoğrafyaya olan sevgisinin bir göstergesidir.

Having retired from the Department of Geography, Faculty of Science and Letters of the Marmara University in 2013, Prof. Dr. Ali Selçuk Biricik has been one of the esteemed lecturers very well known by the world of geography with his professional life that lasted almost half a century, and made significant contributions to the science of geography in many fields. This paper deals with Biricik’s educational background, professional life, scientific personality, contributions to the geography education, administrative and academic functions briefly, and his scientific publications have been introduced with clear identifications. Undoubtedly, he will continue to conduct studies in different parts of our country, and in various fields of the science of geography, and to be together with his colleagues and students. As a matter of fact, even though he has retired, the fact that he continues his studies with the same passion is the indication of his respect towards his profession and love for geography.
Prof. Dr. Ali Selçuk Biricik’s Professional Life and his Contributions to the Geography Science
Keywords: Eğitim, Eğitim Araştırmaları